Against the Monsters within: Resisting Patriarchy, Women Subordination and Morbid Culture in Benedict Binebai’s Karena’s Cross - Raphael Chukwuemeka Onyejizu (University of Chitral Journal of Linguistics and Literature, 2020)
African drama and theatre discourse on gender relations often address some cultural issues as salient factors that undermine the female quest to transcend marginal and debilitating spaces through self-emancipation and education. This paper examines these peculiarities and discusses the underpinnings of patriarchy and the female ordeal, particularly as this relates to the girl-child such as sexual abuse, underage marriage, female genital mutilation, sex-trafficking and other constraints manifest against her will to survive in a patriarchal society. This paper is inspired by the fact that the female child still struggles to grapple with numerous challenges in a hegemonic culture. Using the descriptive method of analysis, the paper adopts the feminist approach to analyze this dilemma head-on. It makes a critical contribution to the girl-child and explores the dominant cultural milieu prevalent in the African rural society that appears to have fostered the course of her numerous predicaments. The paper submits that the African female and the girl-child in rural settings can successfully break through such hegemonic and disconcerting yokes by sheer resilience.